A retrospective analysis of Vulva Carcinoma patients treated at a cancer center in Nepal in ten years - Rana , Sarita; Acharya , Bijay Chandra; Jalan, Aditya; Pandey , Manju; Subedi , Hemnath; Dhungana, Ishan; Lamichhane , Nirmal; Shrestha, Binuma (Europasian Journal of Medical Sciences, 2021)
Background: Vulvar cancer is not an uncommon condition and accounts for 4-6% of genital tract cancers in females. More than ninety percent of such cancers are squamous cell type. In this study, we attempted to analyze the demographic and clinicopathological profile of vulvar cancer cases over 10 years. Methods: This descriptive study was conducted at BP Koirala Memorial Cancer hospital, Nepal. The demographic and clinicopathological profile of all patients diagnosed as Squamous Cell Carcinoma of Vulva between January 2009 to December 2019 were evaluated. Tumour staging was standardized according to the International Federation of Gynecology and Obstetrics (FIGO) system. All the quantitative data and qualitative variables were analysed with SPSS software (SPSS Inc., Chicago, IL, USA, version 16.0). Results: Among 77 patients, the median age was 55 years. Most were married (97.4%, n=75), and were illiterate (61%, n=47). Forty-five percent (n=35) were smokers and sixty percent (n= 46) were from terai area. Most patients presented with growth (88.31%, n=68) over vulvar region. Palpable inguinal lymph nodes were present in 80.5% (n=62) of patients. Forty percent (n=31) were diagnosed at clinical stage III followed by stage IV (27.2% n=21). The most common histological grading was moderately differentiated SCC (50.6%, n=39). Management was Surgery in 72.72% (n=56) patients and rest 27.2% (n=21) sent for chemo radiation. The most common postoperative complications were lymphedema (27%, n= 15) and wound infections (12.5%, n=7). Recurrence was observed in 28.57% (n=22) of cases. Conclusions: Vulvar cancer is common among middle-aged married women. The disease may be locally advanced at diagnosis. Public awareness of the disease severity and timely health care seeking behavior is still lacking. Surgery with or without chemo-radiation is the treatment modality DOI: https://doi.org/10.46405/ejms.v3i2.381